IMPORTANCE OF AUDIT EVIDENCE IN IMPLEMENTATION OF INTERNAL AUDIT ACTIVITIES IN THE PUBLIC SECTOR (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article describes the role and importance of audit evidence during the implementation of internal audit activities in the public sector. Also, the explanatory aspects that should be taken into account when obtaining audit evidence, the selection of audit evidence, and the methods of obtaining evidence are described.